CDR 2019
DOI: 10.20517/cdr.2019.56
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer stem cells properties and features: evidence of interleukin-8 involvement

Abstract: Colorectal cancer (CRC) still remains a disease with high percentage of death, principally due to therapy resistance and metastasis. During the time the hypothesis has been reinforced that CRC stem cells (CRCSC) are involved in allowing intratumoral heterogeneity, drug escape mechanisms and secondary tumors. CRCSC are characterized by specific surface markers (i.e., CD44 and CD133), signaling pathways activation (i.e., Wnt and Notch) and gene expression (i.e., Oct4 and Snail), which confer to CRCSC self-renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…Tumor-derived IL-8 displays autocrine activities, sustaining CRC tumorigenesis and treatment resistance. IL-8 maintains and promotes cell stemness through Snail-dependent EMT, among other mechanisms ( Figure 1 B) [ 10 ]. On the other hand, Oct4, a specific marker of CRC stem cells, promotes IL-8 upregulation [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor-derived IL-8 displays autocrine activities, sustaining CRC tumorigenesis and treatment resistance. IL-8 maintains and promotes cell stemness through Snail-dependent EMT, among other mechanisms ( Figure 1 B) [ 10 ]. On the other hand, Oct4, a specific marker of CRC stem cells, promotes IL-8 upregulation [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the canonical effects caused by tumor-derived IL-8, VEGF-independent angiogenesis is one of most characterized; by binding CXCR1 and CXCR2 expressed by endothelial cells, soluble IL-8 induces endothelial cell proliferation and capillary tube organization [ 9 ]. IL-8 also contributes to the epithelial-to-mesenchymal transition (EMT) and cancer stem cells (CSC) generation and maintenance; our group recently reviewed the molecular mechanisms by which IL-8 promotes stemness in the CRC niche [ 10 ]. On the other hand, immune cell populations also contribute to IL-8 production, both within the TME and systemically [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that IL-8 is an inflammatory cytokine released from many types of cells, such as macrophages, stromal, endothelial, epithelial and tumor cells, involved in promoting EMT, angiogenesis, tumor growth, metastasis and the immunosuppressive microenvironment in human cancers including CRC (105)(106)(107)(108)(109)(110)(111)(112). Previous studies also revealed that a high expression level of IL-8 in human CRC tissues, mediated by IL-8 functional receptors IL-8RA and IL-8RB (43,110,(113)(114)(115), was particularly associated with the properties and features of CSCs (51,113). Recent studies have confirmed that IL-8 is an of the important modulators of the biological behavior of CSCs e.g., stemness properties that contribute to CRC recurrence and metastasis (42,(113)(114)(115)(116)(117).…”
Section: Il-8mentioning
confidence: 91%
“…Previous studies also revealed that a high expression level of IL-8 in human CRC tissues, mediated by IL-8 functional receptors IL-8RA and IL-8RB (43,110,(113)(114)(115), was particularly associated with the properties and features of CSCs (51,113). Recent studies have confirmed that IL-8 is an of the important modulators of the biological behavior of CSCs e.g., stemness properties that contribute to CRC recurrence and metastasis (42,(113)(114)(115)(116)(117). These regulatory effects were found to be mediated via a direct impact on the generation and maintenance of CSCs (42, 113-117) through its functional receptors IL-8RA and IL-8RB expressed in CSCs (43,110,(113)(114)(115).…”
Section: Il-8mentioning
confidence: 91%
See 1 more Smart Citation